2017
DOI: 10.1007/s13337-017-0384-6
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide sequence analyses of coat protein gene of peanut stunt virus isolates from alfalfa and different hosts show a new tentative subgroup from Iran

Abstract: Alfalfa cultivars grown in 14 provinces in Iran were surveyed for the relative incidence of peanut stunt virus (PSV) during 2013-2016. PSV were detected in 41.89% of symptomatic alfalfa samples and a few alternate hosts by plate-trapped antigen ELISA. Among other hosts tested only , and were found naturally infected with PSV. Twenty five isolates of PSV were chosen for biological and molecular characterizations based on their geographical distributions. There was not any differences in experimental host range … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Sequences obtained by Sanger were used for assignment to pathotypes/subgroups according to recent comprehensive studies of BCMV [ 27 ], CMV [ 28 ], and PSV [ 29 ]. The results revealed that 79% of BCMV sequences fall into pathotype VII, sharing 97.7–99.2% identity with NL-4 strain (DQ666332) [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sequences obtained by Sanger were used for assignment to pathotypes/subgroups according to recent comprehensive studies of BCMV [ 27 ], CMV [ 28 ], and PSV [ 29 ]. The results revealed that 79% of BCMV sequences fall into pathotype VII, sharing 97.7–99.2% identity with NL-4 strain (DQ666332) [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…To compare with previous phylogenetic works in the literature, reference sequences of strains detected in this investigation were aligned and analyzed with those included in the most recent phylogenetic studies on BCMV [ 27 ], CMV [ 28 ] and PSV [ 29 ]. Phylogeny of BCMV, PSV and CMV isolates infecting Lamon bean plants was reconstructed by adopting the maximum likelihood (ML) method as implemented in Geneious—R10 (Biomatters Ltd., Auckland, New Zealand).…”
Section: Methodsmentioning
confidence: 99%